evidence newfound of the Sassanid presence in the Central Plateau (evaluation of archaeological evidence and written texts) Case Study Shirkooh area Nain - milad baghsheikhi; Mohammad Esmaeil Esmaeili Jelodar; alireza khosrowzadeh; mehdi sheikhzadeh; alamdar alian (مجله مطالعات ایرانی, 2019)
1.Introduction The location of Isfahan province in a highway which connects the north to the south and the east to the west has created a suitable situation for transformation and innovation of art and architecture. Naein in Isfahan province is a town located in the desert margin. Pakooh region is one of the villages of Naein located in the northwest. The ancient site of Shirkooh is in the vicinity of Separo Village located 6 kilometers away from the west of it. Due to its strategic location, this region has always been suitable for human settlements. Among the evidence which represents a Sassanian settlement in Shirkooh, one can mention a fortress, a Čahārṭāq (four arches), and Soffeh (Terrace platform).It is likely that in the past this region was located near a major communication highway. Hence, the Sassanid constructed a fortress on top of Shirkooh (Zardkooh).